UNIVERSAL DECLARATION OF HUMAN RIGHTS THE PRINCIPLE OF JUSTICE THAT HUMANIZED THE WORLD - Ortiqov, Olimjon; Baltabaev, Nurlan (Science technology&Digital finance, 2023)
This article notes the current significance of the UN Universal Declaration of human rights and the provisions of this document are expressed in the norms of the Constitution of the Republic of Uzbekistan, national legislation, which provides for the reliable protection of individual, political, economic, social and cultural rights and freedoms of a person.